Detection of Toxoplasma gondii in Cord Blood Samples from Neonates in Tehran, Iran - Moloud NAHVI; Saeedeh SHOJAEE; Hossein KESHAVARZ; Mahboobeh SALIMI; Mehdi MOHEBALI (Tehran University of Medical Sciences, 2019)
Background: Toxoplasmosis is an infectious disease caused by the coccidian protozoan parasite Toxoplasma gondii. The infection is life-threatening in congenital form because of transmission of the parasite from mother to fetus. In order to investigate the prevalence of congenital toxoplasmosis, the present study was performed for detection of IgG and IgM antibodies in cord blood samples of newborns by ELISA method in Tehran, Iran. Methods: This cross-sectional survey was carried out on 1000 cord blood samples collected from Shahid Mostafa Khomeini Hospital in Tehran, Iran in 2015. Sera were separated and evaluated for the presence of IgG and IgM antibodies against T. gondii by ELISA method. At the same time, whole cord blood samples were stored at -20 °C for complementary PCR test. Results: From 1000 cord blood serum samples 198 cases (19.8%) were positive for anti T. gondii IgG antibody. IgG positive samples were examined for IgM antibody, among them 1 sample had borderline levels of IgM antibody. PCR was performed for this sample but no positive result was seen. Conclusion: Although congenital toxoplasmosis is of importance, no acute form of infection was seen in pregnant women in this study.